(untitled) (Groundings Undergraduate, 2023)
This paper examines the ways in which contemporary female musicians use their art to explore the impact of sexual violence. Through the utilisation of qualitative research and thematic analysis, the study analyses the lyrics of songs written by seven artists: Lady Gaga, Natalie Grant, Tori Amos, Ashe, Rapsody, Jolin Tsai and Ana Tijoux. The analysis focuses on examining several key themes such as the use of metaphor, the psychological experiences of survivors, and the representation of marginalised voices in the lyrics. The findings of the study highlight the powerful role that music can play in giving voice to the experiences of survivors and challenging cultural narratives that contribute to rape culture. Content sensitivity warning: themes of sexual assault, violence and trauma.